Elucidating the Electronic Synergetic Effects in Heteroatomic Doped Fen4-C-N-R (R= -F, -Cl, -Br) Oxygen Reduction Catalysts - Zagal-Moya, J; Zagal-Moya, J; Ponce-Hormazabal, I; Venegas-Toledo, R (Elsevier Ltd, 2023)
The structural and electronic characteristics of FeN4 are the determining factors in the catalytic performance of heat-treated Fe-N-C materials, as they serve as active sites. The insertion of heteroatoms as co-dopants (B, S, halogens) can induce electronic effects in the carbon matrix that improves their ORR catalytic activity. Therefore, it has become essential to combine experimental studies with DFT approaches to rationally design this type of catalyst. In this work, we evaluated by means of first principle DFT approaches, the ORR activity for the Fe(phen)2N2 moiety including atoms/functionalities with different atomic radii and electronegativity, to resemble co-doped Fe-N-C-R catalysts. The results showed that the inclusion of halogens heteroatoms (-F, -Cl, and -Br) in the graphitic N[sbnd]C surrounding the FeN4 core could improve its ORR activity in terms of Fe-O2 binding energy that is related to the Fe(III)/Fe(II) formal potential and, in consequence, with the on-set potential for the ORR. The high expected ORR activity is obtained for bromide co-doped FeN4 catalyst (FeN4-C-Br) since -Br atoms act synergistically, inducing long- and short-range electronic effects over both the FeN4 unit and N-pyridinic-like functions that change the electronic distribution over the aromatic N[sbnd]C structure modulating the Fe acidity, Fe-O2 binding, and Fe-O2 orbital interaction. © 2023